EDUKASI PEMANFAATAN DAN PELESTARIAN HUTAN MANGROVE DI KAMPUNG MAIBO KLALIN IV KABUPATEN SORONG - Habel S.J. Rieuwpassa (COVIT (Community Service of Health), 2022)
Abstract: Paying attention to the potential damage to mangrove forests in the area of Kampung Maibo Klalin IV, Kelurahan Klabinain, Aimas District, Sorong Regency, if left unchecked it will have a negative impact on the environment and the people who live in that place. In addition to carrying out mangrove forest reforestation activities, in our opinion, the people who use mangrove forests need to be empowered to realize the importance of mangrove forests for marine habitat life, an environment that can actually provide solutions for empowering the local economy. The result of this activity is to find out the extent, causes and consequences of the damage to the mangrove forest that has occurred. Then the team conducted education to plant mangrove trees properly and correctly. Keywords: Mangrove forest, reforestation, local economic empowerment